2011
DOI: 10.1523/jneurosci.0273-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Human Motor Cortex Alters Generalization Patterns of Motor Learning

Abstract: It has been hypothesized that the generalization patterns that accompany learning carry the signatures of the neural systems that are engaged in that learning. Reach adaptation in force fields has generalization patterns that suggest primary engagement of a neural system that encodes movements in the intrinsic coordinates of joints and muscles, and lesser engagement of a neural system that encodes movements in the extrinsic coordinates of the task. Among the cortical motor areas, the intrinsic coordinate syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 69 publications
(92 reference statements)
2
43
2
Order By: Relevance
“…tDCS-related effects on adaptation have also been studied in young healthy adults (Avila et al, 2015;Galea et al, 2011;Herzfeld et al, 2014;Hunter, Sacco, Nitsche, & Turner, 2009;Orban de Xivry et al, 2011) (Table 3). Galea and colleagues (2011) compared the effects of anodal tDCS applied to the cerebellum versus M1 during concurrent adaptation to 30-degree rotation of visual feedback (Galea et al, 2011).…”
Section: Adaptationmentioning
confidence: 99%
“…tDCS-related effects on adaptation have also been studied in young healthy adults (Avila et al, 2015;Galea et al, 2011;Herzfeld et al, 2014;Hunter, Sacco, Nitsche, & Turner, 2009;Orban de Xivry et al, 2011) (Table 3). Galea and colleagues (2011) compared the effects of anodal tDCS applied to the cerebellum versus M1 during concurrent adaptation to 30-degree rotation of visual feedback (Galea et al, 2011).…”
Section: Adaptationmentioning
confidence: 99%
“…It has been suggested that this effect may be due to a gating mechanism, i.e., the possibility of inducing additive neuroplastic changes by modulating the excitability of the target neurons [9,10]. In the motor system, evidence that A-tDCS over the primary motor cortex (M1) facilitates learning has been This work was supported by a grant from the Italian Ministry of Health RC 2013. found with many different tasks, e.g., the isometric pinch force task [11,12], implicit sequence learning [13], explicit sequence learning [14,15], visuo-motor learning [16] and force-field tasks [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism underlying tDCS induced ongoingeffects and aftereffects both remain controversial, a few human studies have demonstrated that anodal tDCS increases cortical excitability over primary motor cortex (M1) which plan and execute movements associated with other motor areas [19], [21], and two recent studies reported that this effect could enhance motor skill acquisition ability [23] and alter generalization patterns of motor learning [24], [25]. Based on these findings, the possibility of an enhancement of movement, which is related cortical activation by tDCS on motor cortex, can be reasonably considered.…”
Section: Introductionmentioning
confidence: 99%